Activity Concentrations of Sr-90 and Cs-137 in Seawater and Sediment in the Gulf of Tonkin, Vietnam - Trong-Ngo Nguyen; Quang-Thien Tran; Van-Phuc Nguyen; Nhu-Sieu Le; Son-Hai Phan; Xuan-Thang Le; Thi-Thu-Hang Vuong; Van-Phu Nguyen; Đinh-Tung Nguyen; Đinh-Khoa Tran; Minh-Đao Nguyen; Quang-Trung Phan; et al. (Journal of Chemistry)
In this study, we measured the activity concentrations of Cs-137 and Sr-90 in surface seawater and surface sediments at the Tra Co, Bach Long Vi, and Ky Anh locations in the Gulf of Tonkin, Vietnam, from December 2018 to October 2019. The average activity at the selected locations was 1.22, 1.43, and 1.33 Bq/m3 for Cs-137 and 0.88, 1.17, and 1.09 Bq/m3 for Sr-90 in surface seawater samples and 0.74, 1.01, and 0.81 Bq/kg dry for Cs-137 and 0.49, 0.49, and 0.43 Bq/kg dry for Sr-90 in sediment samples. The ratio of the average activity concentration (Cs-137/Sr-90) in the surface seawater was 1.42, 1.22, and 1.22 at the Tra Co, Bach Long Vi, and Ky Anh locations, respectively. These are somewhat low compared to the global ratios (1.6 and 1.8). Meanwhile, Cs-137/Sr-90 ratios in the sediment samples at the selected locations were 1.51, 2.06, and 1.88, respectively, which is equal to or greater than the corresponding value for global sedimentation according to the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). Correlations between Sr-90, Cs-137, and organic carbon content were detected in this study. The results showed that Cs-137 has a high correlation with the organic carbon content in sediment, while Sr-90 has a low correlation.